A IMPLEMENTASI PROGRAM PEMERINTAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MISKIN DI KABUPATEN BERAU - Mawi, Tiarasari (ECO-BUILD, 2017)
Policy implementation Saves Family Welfare Program (PSKS) in Berau can be seen through several aspects in the smooth implementation among others Communication that is related to how the policy is communicated to the organization and or public, the ability and skills of staff / employees, information regarding the information submitted or received should be clear so as to facilitate or expedite the implementation of the policy or program, the Authority is the right to make decisions, Infrastructure relating to facilities in the implementation of policy, funding is financing the implementation of policies. The purpose of research is to obtain information regarding policy implementation PSKS. This type of research is a qualitative research, in which the source data is obtained from informants and documents. In PSKS implementation in order to achieve the welfare of the poor in Berau, there are some problems faced by PT.Pos, where lack of infrastructure (vehicle) in channeling funds to the sub-district PSKS who do not have a post office, then the number of recipients is not in accordance with the amount of data on poverty the new one.